Cyber Peace Charting a Path Toward a Sustainable, Stable, and Secure Cyberspace - Shackelford, Scott J.; Douzet, Frederick; Ankersen, Christopher (Social Sciences, 2022)
Cyberspace is increasingly vital to the future of humanity and managing it peacefully and sustainably is critical to both security and prosperity in the twenty-first century. These chapters and essays unpack the field of cyber peace by investigating historical and contemporary analogies, in a wide-ranging and accessible Open Access publication.